Animal remains from Neolithic Lameiras, Sintra: the earliest domesticated sheep, goat, cattle and pigs in Portugal and some notes on their evolution - Davis, Simon J.M. (2019)
The fauna of Neolithic Lameiras includes abundant sheep. Many could be securely identified by applying criteria described by the late Joachim Boessneck as well as metrical methods. Sheep bones from Early Neolithic contexts, several dated directly via 14C, pinpoint the arrival here, 5450 cal BC, of this exotic animal three thousand years after its domestication 5000 km to the east. Thus sheep were transported at a rate of 1,6 km per year – considerably faster than suggested by the ‘wave of advance’ theory. It therefore seems probable that part of the journey was undertaken by ship. Most of the mammal remains identified at Lameiras belonged to domesticated forms and besides sheep and some goat, they include cattle and pig. Zooarchaeologically there is little difference between Early and Late Neolithic. However the Neolithic spectrum of species contrasts with that from a small assemblage in the underlying Mousterian level as well as other pre-Neolithic assemblages in Portugal. It is possible that in southern Portugal the adoption of animal husbandry was sudden. Measurements of the remains of Canis, Bos, Ovis, Capra and Sus compared with an increasingly large corpus of data from the South-Western part of the Iberian Peninsula indicate several occasions when these animals underwent size changes. Bos, Capra and Canis were considerably larger in the Pleistocene – a size difference now documented in other regions. Besides a Pleistocene-Holocene reduction in size, they underwent a further diminution associated with their domestication. It is possible that aurochs and wild boar recovered some of their former size after the Neolithic, perhaps due to a relaxation of hunting pressure after the Mesolithic. Domestic sheep, goats and cattle increased in size in more recent times perhaps reflecting Moslem and Christian improvements.